Metode Eklektik Dalam Pembelajaran Bahasa Arab: Integrasi Strategis untuk Hasil Maksimal - Supriyanoor, Supriyanoor; Hamidah, Hamidah; Marsiah, Marsiah (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The eclectic method is a method that combines various existing learning methods, such as grammar-translation, direct, audiolingual, and communicative methods, by considering student needs, learning contexts, and instructional objectives. This study aims to describe the application of the eclectic method in Arabic language learning at MTs Normal Islam Putra Rakha Amuntai. This study uses a descriptive qualitative method with a case study approach. In this study, several research instruments were used in the form of observation, documentation, and structured interviews sourced from Arabic language teachers and eighth-grade students in the 2024-2025 academic year at MTs Normal Islam Putra Rakha Amuntai. The results of the study indicate that the use of the eclectic method in Arabic language learning, by combining various teaching methods flexibly, makes the learning atmosphere more varied and responsive to the needs and backgrounds of various students. This method can increase students' motivation and understanding of Arabic language material. However, there are several obstacles, such as limited learning time, supporting resources, and differences in students' initial abilities. Arabic language teachers can use eclectic methods to adapt learning strategies to classroom dynamics and student circumstances.